2012
DOI: 10.5829/idosi.ijee.2012.03.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Knife Bevel Angle, Rate of Loading and Stalk Section on Some Engineering Parameters of Lilium Stalk

Abstract: Some physical and mechanical property testing of main stalks of Lilium was conducted to provide information for future automatic machine design. Shear, compression and bending properties of Lilium stalks were determined with using a universal testing machine. The experiments were conducted at three rate of loading levels from 30 to 50 mm/min, three knife bevel angle levels from 30 to 60 degree and at two levels the stalk; upper and lower. The results showed that all the mentioned above parameters had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The laver and rose flower stems were compressed at low cutting rates while resisting shearing by the knife. However, at high cutting rates, the elastic walls of the cells did not have enough time to transmit shear forces to the viscous fluid inside the cells, resulting in a decrease in shear strength [42,43]. The same findings were also reported by Hassan-Beygi for the shear strength of saffron stalks [41].…”
Section: Effect Of Loading Rate On Shear Strength and Adhesiveness Of...supporting
confidence: 72%
See 1 more Smart Citation
“…The laver and rose flower stems were compressed at low cutting rates while resisting shearing by the knife. However, at high cutting rates, the elastic walls of the cells did not have enough time to transmit shear forces to the viscous fluid inside the cells, resulting in a decrease in shear strength [42,43]. The same findings were also reported by Hassan-Beygi for the shear strength of saffron stalks [41].…”
Section: Effect Of Loading Rate On Shear Strength and Adhesiveness Of...supporting
confidence: 72%
“…Meanwhile, several studies have also reported the effect of loading rate on mechanical properties of agricultural crops. The crops included saffron [41], sorghum [42] and lilium [43]. In general, the biomechanical properties of algae, plant stem stalks, and leaves are strongly influenced by factors such as origin and harvest times.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used cutters in tea pluckers include the reciprocating cutter, disk cutter, and flail-type cutter. Compared with the disk and flail-type cutters, the reciprocating cutter has a simpler structure and a wider range of adaptations [6][7][8]. Besides, it is important to optimize the structural parameters of the reciprocating cutter to improve its cutting performance.…”
Section: Introductionmentioning
confidence: 99%